The duty-right to apostolate (remarks on canon 211) - LE TOURNEAU, DOMINIQUE (Prawo Kanoniczne, 2014)
The faithful have the native right o proclaiming the faith, right which concerns first of all the whole Church, as it was reminded by the II Vatican Council. As far as the faithful are concerned, this duty-right is connected with can. 210 about sanctity of life and can. 225 §1 on working to expand the divine message of salvation throughout the entire world. The Author deals also with the notion of proselytism, which is not always correctly understand. Part II of the present work present “the actors of apostolate”. To exercise their function in the Church and in the world, their right to associate must be recognized and protected so that they be able to do individual apostolate, which does not prevent them from participating in the apostolate organised by the hierarchy of the church. Canon 211 appears to be an essential norm in the Code, and is a direct consequence of secularity of lay people. Anyway, the faithful are subject to a certain control by the diocesan bishop as moderator of the entire ministry of the Word (can. 756 § 2). Concluding, the Author deplore that a true protection of the rights of the faithful is still largely missingin the church.